A reply to critics. Issue 3 (1st March 2016) - Bevir, Mark
Abstract : This paper is a response to Gary Marshall, Colin Macleod, and Amit Ronʼs careful discussions of my book, A Theory of Governance . The word "governance" is used in two contexts that might initially appear to have little relation to each other. Governance is used, first, as a general term to discuss abstract theories of coordination and organization. And governance is used, second, to narrate a historic shift in public organization and action.A Theory of Governance offers a decentered theory (part one of the book) that seeks to combine a general analysis of various forms of coordination and organization (part two of the book) with a narrative of recent changes in public organization and action (part three of the book). In this paper, I emphasize that decentered theory turns to historical genealogies to avoid determinism, reification, and foundationalism. Contemporary governance is, therefore, the variegated product of contests over meanings, specifically those reform agendas that have sought to spread markets and networks. I conclude the essay with some reflections on the nature and importance of democratic innovations within governance.